Bacteriocin-encoding genes and ExPEC virulence determinants are associated in human fecal Escherichia coli strains - Micenková, Lenka; Štaudová, Barbora; Bosák, Juraj; Mikalová, Lenka; Littnerová, Simona; Vrba, Martin; Ševčíková, Alena; Woznicová, Vladana; Šmajs, David (BMC microbiology, 2014)
BACKGROUND: A set of 1181 E. coli strains of human fecal origin isolated in the South Moravia region of the Czech Republic was collected during the years 2007-2010. Altogether, 17 virulence determinants and 31 bacteriocin-encoding genes were tested in each of them. RESULTS: The occurrence of bacteriocin-encoding genes was found to be positively correlated with the occurrence of E. coli virulence factors. Based on the presence of virulence factors and their combinations, E. coli strains were classified as non-pathogenic E. coli (n = 399), diarrhea-associated E. coli (n = 179) and ExPEC strains (n = 603). Non-pathogenic and diarrhea-associated E. coli strains had a low frequency of bacteriocinogeny (32.6% and 36.9%, respectively). ExPEC strains encoding S-fimbriae (sfa), P-fimbriae (pap) and having genes for aerobactin biosynthesis (aer, iucC), α-hemolysis (α-hly) and cytotoxic necrosis factor (cnf1) were often bacteriocinogenic (73.8%), had a high prevalence of bacteriocin multi-producers and showed a higher frequency of genes encoding microcins H47, M, V, B17 and colicins E1, Ia and S4. CONCLUSIONS: The occurrence of bacteriocin-encoding genes and ExPEC virulence determinants correlate positively in E. coli strains of human fecal origin. Bacteriocin synthesis appears to modulate the ability of E. coli strains to reside in the human intestine and/or the virulence of the corresponding strains.
Keywords: Virulence Factors; Genotype; Female; Bacteriocins; feces; Feces; Escherichia coli; ženské pohlaví; DNA bakterií; bakteriální geny; DNA, Bacterial; lidé; Molecular Sequence Data; genotyp; molekulární sekvence - údaje; Male; Czech Republic; bakteriociny; Sequence Analysis, DNA; Česká republika; Genes, Bacterial; mužské pohlaví; sekvenční analýza DNA; faktory virulence; Humans